Persepsi mahasiswa calon guru terhadap penggunaan Phet Colorado untuk memfasilitasi kemampuan representasi visual - Depi Oktasari; Dian Aulia; Jumadi Jumadi; Zera Nadiah Ferty; Ismet Ismet; Sardianto Markos Siahaan (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2020)
Penelitian ini bertujuan untuk mengetahui presepsi mahasiswa calon guru fisika terhadap penggunaan PhET Colorado dalam memfasilitasi kemampuan representasi visual mereka dalam pembalajaran fisika. Adapun jenis penelitian ini merupakan penelitian deskriptif dengan menggunakan pendekatan kualitatif. Subyek penelitian merupakan mahasiswa magister pendidikan fisika Universitas Negeri Yogyakarta semester pertama tahun ajaran 2017/2018. Hasil penelitian dari 20 responden  menunjukkan bahwa 50% responden sangat tertarik menggunakan  PhET Colorado, dengan persepsi mahasiswa terhadap kemampuan representasi visual menggunakan PhET Colorado sebesar 85%, penggunaan PhET Colorado dianggap siswa mampu memfasilitasi kemampuan representasi visual mereka dalam pembelajaran fisika.  AbstractThe demands of 21st century skills highlighted the importance of cooperation between teachers and students to achieve the expected skill. Pedagogical knowledge of teachers in teaching and technology into things that need to be developed. Pedagogic ability of teachers in the use of technology can be a potential to develop students' abilities argument. This study aims to develop students' ability argumentation through pedagogical knowledge of teachers in using technology. The technology used is the result of the development of student worksheets 3D PageFlipp Impulse and Momentum material. The purpose of this study to look at the ability of students through the application of scientific argumentation (Technological Pedagogic Knowledge) TPK teachers in the classroom. This research is descriptive research. The data collection capability student argumentation performed by administering a written test. The subjects were students of class X at SMAN 1 Yogyakarta Prambanan. Rate scientific argumentation ability of students refers to Toulmin Argumentation Pattern (TAP). The results showed that the complexity of argumentation ability of students still at low level . These results suggest that the ability of the student arguments need to be improved.